Trees, rivers and gods: Paganism in the work of Martin Heidegger. (June 2018) - Travers, Martin
The concern that Heidegger voiced in his later work for the plight of nature in a world dominated by technological rationality and commercial exploitation has often been seen as sign of his commitment to environmental ethics. This paper argues that the roots of Heidegger's concern lay elsewhere, most notably in his identification with the beliefs and practices of Germanic paganism. Beginning with a discussion of Heidegger's notion of the 'Geviert' (the 'fourfold'), this paper examines how Heidegger drew upon the elemental tropes of the pagan mind, most noticeably those that celebrated water, land and forest, to ground his appropriation of nature in an ethos of spiritualized naturalism.